(untitled) (Research, Society and Development, 2022)
The presence of pigeons in places with large numbers of people becomes a serious health problem, as diseases such as cryptococcosis can arise, potentially fatal, cosmopolitan infectious fungal disease caused by the fungus Cryptococcus neoformans, found in bird droppings, especially of pigeons, the urban ecosystem has become favorable for the permanence of these birds, becoming an environmental and public health problem. For this reason, this study aimed to evaluate the incidence of Cryptococcus neoformans in pigeon droppings in the city of Porto Velho. The collections were made in three strategic locations in the city of Porto Velho and on the Campus of the Federal University of Rondônia. The samples were preserved in formalin and analyzed at the Centro Interdepartamental de Biologia Experimental e Biotecnologia (CIBEBI) through parasitological stool examination (EPF) techniques by spontaneous sedimentation and density flotation. For analysis, the slides with samples were submitted to two forms of staining, with lugol and china ink, morphological observation under light microscopy at 100x and 400x magnification. The results confirm the sedimentation method as the most suitable and the china ink staining as the most specific for diagnosis. Cryptococcus neoformans was identified in 25% of the samples in both urban and peri-urban locations. Therefore, it’s concluded that the population is exposed to contamination in public environments, and a policy of diagnostic analysis in health care units is necessary so that fungal infections aren’t neglected.